Reconfiguration of Distribution Power Systems Using Heuristic Optimization Algorithms - Diana Akmayeva; Umut Emre Uzun; Nihat Pamuk (Turkish Journal of Electrical Power and Energy Systems)
Reconfiguration of the power distribution system allows for minimal real power losses and compliance with the required bus voltage limits of the power system. This paper proposes the network reconfiguration of the IEEE 33-bus radial distribution system using heuristic optimization algorithms. This problem-solving approach has the advantage of identifying the optimal system configuration solution by evaluating all possible solutions to the problem. The least power losses, voltage deviation, and compliance with the required bus voltage limits of the power system determine the optimal solution. To solve this problem, three types of heuristic optimization algorithms are used: Particle Swarm Optimization (PSO), Multi-Verse Optimization (MVO), and Grey Wolf Optimization (GWO). Using heuristic optimization algorithms to solve the reconfiguration problem, the active power losses of the power distribution system decreased by 46%. The optimal results obtained using the GWO algorithm are compiled in less time than other algorithms.